Towboat on the Ohio - Casto, James E. (Book collections on Project MUSE., 2010)
To get a personal look at what it is like to work on the Ohio River, newspaperman James E. Casto spent eight days aboard the Blazer as it traveled the Ohio from Huntington, West Virginia, to Pittsburgh, up the Allegheny and the Mongahela, and then back to Huntington. The Paul G. Blazer, a gleaming white towboat owned and operated by Ashland Oil, pushes a group -- or ""tow, "" as the rivermen call it -- of nine barges on this trip. Along the way, Casto introduces us to Captain Ronnie Davis, pilot Ronnie Burge, engineer Steve Bellomy, the mates, the deckhands, and the cook, as well as the river.